Goldie and the three hares - Palatini, Margie (Katherine Tegen Books, 2010)
When Goldilocks, running from the three bears, falls down a rabbit hole and hurts her foot, a family of hares tries to help but she proves to be a very loud, demanding, and tenacious guest.